Comparing the emotional and cognitive components of initial trust formation in air traffic controller-autonomy teams - Pushparaj, Kiranraj (2022)
The use of intelligent decision aids in Air Traffic Management is recommended to manage the exponential rise in global air traffic. Consequently, trust, which is one of the main drivers of how Air Traffic Controllers use such decision aids, has become an important area of research. It has been suggested that there is a strong emotional influence in the formation of Human-Human Trust, and it is unclear if this paradigm is valid for Human-Autonomy Trust. The extent of the cognitive and emotional components in the initial trust relationship between Air Traffic Controllers and a simulated conflict detection autonomous decision aid was examined with the use of functional Magnetic Resonance Imaging. The results confirmed that the emotional component showed higher activation than the cognitive component for the initial formation of trust between Air Traffic Controllers and autonomous decision aids.